Effects of α2-adorenoceptor agonist dexmedetomidine on respiratory rhythm generation of newborn rats. (15th June 2015) - Tsuzawa, Kayo; Minoura, Yoshino; Takeda, Shinhiro; Inagaki, Katsunori; Onimaru, Hiroshi
Highlights: Dexmedetomidine is clinically used as an analgesic and sedative agent. We examined the effects of this drug on respiratory activity and spinal reflex responses. Dexmedetomidine (0.1–10 μM) dose-dependently depressed respiratory rhythm. This drug depressed spinal reflex response at a lower concentration range (0.1–1 nM). These depressions were reversed by α2-adorenoceptor antagonist atipamezole. Abstract: Dexmedetomidine, an α2-adrenoceptor agonist which has a slight side effect on breathing, is clinically used as an analgesic and sedative agent. Previous studies have shown depressing or modest effects of α2-adorenoceptor agonists on respiratory rhythm generation in newborn rat preparation in vitro. In contrast, it was recently reported that dexmedetomidine induced long-lasting activation of respiratory rhythm in brainstem–spinal cord preparation isolated from neonatal mice. In the present study, we examined whether dexmedetomidine induces any effects on respiratory rhythm in brainstem–spinal cord preparation isolated from newborn rats. We also examined the effects of dexmedetomidine on reflex response in the spinal cord, which is presumed to be an indication of nociceptive response. We found that the administration of dexmedetomidine, at the range of 0.1–10 μM, dose-dependently depressed respiratory rhythm and that the inhibitory effect was reversed by atipamezole, an α2-adorenoceptor antagonist. Spinal cord reflex responses were depressed by the application of dexmedetomidine at the range of 0.1–1 nM, a lower concentration than that affecting respiratory rhythm. The inhibitory effect was also reversed by atipamezole. Our findings provide neuronal mechanisms that support the clinical use of dexmedetomidine, which shows sedative and antinociceptive effects with minimal side effects on breathing.